Legal Analysis of Consumer Protection against Companies Not Fulfilling Consumer Obligations - Yusuf, Athiyyah Safirazkiya (Estudiante Law Journal, 2025)
: This study analyzes consumer legal protection against Commanditaire Vennootschap (CV) entities that fail to meet their obligations under Indonesia's Consumer Protection Law (UUPK). It examines challenges in implementing the UUPK and evaluates the effectiveness of legal sanctions in improving CV compliance. Using a qualitative approach, the research employs descriptive analysis and case study methods. Data were gathered from literature reviews, legislation analysis, case studies of CV violations, and interviews with legal experts, business operators, and consumers.  Findings highlight challenges, including limited awareness among CV operators of legal obligations, resource constraints, and low consumer awareness of rights. The effectiveness of UUPK sanctions is hampered by slow enforcement, lack of transparency, and inadequate law enforcement support. Despite administrative and criminal sanctions, these measures have yet to provide a significant deterrent effect, allowing violations to persist.  This study recommends a holistic approach to strengthen UUPK implementation. Key strategies include enhancing law enforcement capacity, providing continuous education for business operators and consumers, and offering incentives for regulatory compliance. Collaboration among government, institutions, business associations, and operators is essential to improve consumer protection and establish a fair, transparent, and sustainable business environment in Indonesia